A healable, recyclable and thermochromic epoxy resin for thermally responsive smart windows. Issue 15 (29th March 2022) - Huang, Qi-Sheng; Zhao, Pei-Chen; Lai, Jian-Cheng; Zhang, Xiao-Peng; Li, Cheng-Hui
Abstract : An epoxy resin modified by coordination between Ni 2+ and imidazole/hydroxyl groups show high mechanical strength and thermal healing/recycling/reprocessing/thermochromic behavior, and might be useful in the field of thermally-responsive smart windows. Abstract : Traditional thermoset polymers such as epoxy resin have strong mechanical strength but are difficult to recycle, reshape and reprocess after being cured. When these materials are damaged, they can only be scrapped, resulting in a waste of resources. Introducing dynamic interactions into thermoset polymers can endow them with recyclable, reshapable and self-healing properties, thus prolonging their lifetime. In this work, we demonstrate that epoxy resin modified by coordination bonds between Ni 2+ ions and imidazole/hydroxyl groups can show high mechanical strength (Young's modulus ranges from 210.4 ± 15.7 MPa to 564.7 ± 9.6 MPa) as well as thermoreversible behaviors (can be healed, reshaped and recovered at 80 °C and 0.1 MPa). More interestingly, due to the structural transformation of the Ni 2+ coordination complex between the four-coordinated geometry and the six-coordinated geometry upon changing the temperature, this material shows reversible thermochromic behavior. Therefore, it has potential applications in the field of thermochromic smart windows.